2015
DOI: 10.1002/dmrr.2724
|View full text |Cite
|
Sign up to set email alerts
|

Association between uric acid, cancer incidence and mortality in patients with type 2 diabetes: Shanghai diabetes registry study

Abstract: In Chinese female diabetic patients, the incidence of cancer increased with serum uric acid levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Conversely, a cohort study of 83,683 participants in Austria found that high levels of serum uric acid were linked to a higher risk of all cancer mortality [9]. Furthermore, a cohort study of 8,274 participants in China found that incidence of cancer increased with serum uric acid levels, but only in females with diabetes [10]. A recent systematic review and meta-analysis of 17 studies on the link between serum uric acid and cancer incidence and mortality was inconclusive [2].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a cohort study of 83,683 participants in Austria found that high levels of serum uric acid were linked to a higher risk of all cancer mortality [9]. Furthermore, a cohort study of 8,274 participants in China found that incidence of cancer increased with serum uric acid levels, but only in females with diabetes [10]. A recent systematic review and meta-analysis of 17 studies on the link between serum uric acid and cancer incidence and mortality was inconclusive [2].…”
Section: Introductionmentioning
confidence: 99%
“…A number of epidemiologic studies have shown that an elevated uric acid level is associated with a wide variety of adverse health outcomes, including hypertension, metabolic syndrome, kidney disease, cardiovascular disease (CVD), and cancer . However, the role of uric acid as an independent risk factor for CVD, cancer, and all‐cause mortality remains a subject of controversy . Some studies demonstrated a positive association between hyperuricemia and cardiovascular mortality , while other studies did not .…”
mentioning
confidence: 99%
“…There have already been suggestions for prediction models to screen newly diagnosed diabetic patients for pancreatic cancer, which include individual characteristics such as age, body mass index, change in body mass index, smoking, use of proton pump inhibitors, and antidiabetic medications, as well as levels of haemoglobin A1C, cholesterol, haemoglobin, creatinine, and alkaline phosphatase . High levels of uric acid were also suggested as a potential marker in diabetic patients …”
Section: Discussionmentioning
confidence: 99%